Factors associated with diabetic retinopathy among type 2 diabetic patients: A hospital based case-control study - Wisit Chaveepojnkamjorn (2018)
© 2015, Southeast Asian Journal of Tropical Medicine and Public Health. All rights reserved. The objective of this study was to determine factors associated with diabetic retinopathy (DR) among type 2 diabetics in Thailand. We conducted a hospital based case-control study in Nakhon Nayok Province, between August 2008 and July 2010. The subjects were comprised of 230 cases (with DR) and 230 controls (without DR) who were gender and age matched. All subjects were interviewed and their medical records were reviewed. Seventy-five percent of subjects were married and 42% were aged 60-69 years. Fifty-five percent had a primary school education, 27% had no occupation and 67% had family income >10,000 Baht per month. On multiple logistic regression analysis, factors associated with DR were: having a fasting plasma glucose (FPG) of 141-160 mg/dl, 161-180 mg/dl and >180 mg/dl [OR = 7.23; 95% confidence interval CI: 2.80-18.72; OR = 4.33; 95% CI: 1.66-11.33, and OR = 3.76; 95% CI: 1.39-10.18], having a HbA1c >9% (OR = 2.26; 95% CI: 1.15-4.43), having a BMI ≥ 30 kg/m2 (OR = 2.09; 95% CI: 1.04-4.19), and having hypertension (OR = 1.80; 95% CI: 1.19-2.71). Elevated blood sugar, blood pressure and body weight are all associated with DR. Further study is needed to determine if controlling these factors could reduce the prevalence of DR.